Determination of predictive factors for difficult laparoscopic cholecystectomy - Bhattarai, Sameer; Bhusal, Ishory (International Surgery Journal, 2021)
Background: Cholelithiasis is the most common biliary pathology, with a prevalence of 10 to 15%. It is symptomatic in approximately 1 to 2% of patients. In about 5 to 10% of laparoscopic cholecystectomy, conversion to open cholecystectomy may be needed for safe removal of gallbladder. Laparoscopic cholecystectomy (LC) may be rendered difficult by various problems encountered during surgery. The objective of this study was to predict difficulty of LC before surgery using the clinical and ultrasonographic criteria. Methods: The present study comprised of 45 cases admitted to National Medical College Teaching Hospital (NMCTH), Birgunj (Nepal) for a period of 12 months from 1st August 2013 to 30th September 2014. The cases confirmed by Ultrasonography were evaluated with following risk factors: age >50 years, male sex, BMI 25.1 to 27.5 and >27.5, previous surgery, prior hospitalization, palpable gall bladder, gall bladder wall thickening, impacted stone, pericholecystic collection and presence of adhesions. Each risk factor was given a score. The total score up to 5 predicted easy, 6 to 10 difficult and more than 10 very difficult. Results: The highest age incidence of Cholelithiasis was in the 2nd to 4th decade and was more common in females. Ultrasonography detected gallbladder stones in all patients, wall thickening in 15 and pericholecystic collection in 8. BMI >27.5 presence of adhesions, male sex and pericholecystic collection were significant predictors of difficult laparoscopic cholecystectomy. Conclusions: Numerous clinical, radiological and pre-operative features make LC sometimes difficult. Early determination of these predictive factors decreases the difficulty that we will be facing with LC.